Novel Approaches to Memory and Aging: The Editorial - Caterina Padulo; Beth Fairfield (Brain Sciences, 2023)
Heightened average life expectancy, which is increasing the number of older adults destined to live alone in the future, is forcing society to acknowledge the strong positive correlation between health costs and age [...]